Silent Resistance Against Androcentric Violence: An Ecofeminist Reading of Sarah Orne Jewett's "A White Heron" - Adhikari, Shreedhar (Literary Studies, 2020)
This paper tries to unravel the cross-cutting dimensions of ecology and feminism for holistic analysis of "A White Heron." The theoretical insights drawn from both schools combine to form the critical lens of ecofeminism to find out the underpinning operational ideology and interpret literaty texts. Greta Gaard and Lori Gruen state: "Standing at the crossroads of environmentalism and feminism, ecofeminist theory is uniquely positioned to undertake a holistic analysis of these problems in both their human and natural contexts" (277). The evolution of interdisciplinary approach and critical practices has led to re-reading and reinterpreting the literary texts ever exploring and widening their dimensions.